2011
DOI: 10.1152/ajprenal.00557.2010
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin deficiency protects against aldosterone-induced inflammation, oxidative stress, and interstitial fibrosis in the kidney

Abstract: Osteopontin (OPN) has been implicated in the pathology of several renal conditions. Recently, we demonstrated in vitro that aldosterone has important roles in collagen synthesis by inducing OPN (Irita J, Okura T, Kurata M, Miyoshi K, Fukuoka T, Higaki J. Hypertension 51: 507-513, 2008). The aim of the present study was to clarify the roles of OPN in aldosterone-mediated renal fibrosis by infusing aldosterone into either wild-type (WT) or OPN knockout mice (OPN(-/-)). We used uninephrectomized mice treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 42 publications
(34 reference statements)
5
46
0
Order By: Relevance
“…38,39 Our recent study showed that high salt-induced kidney damage in KL(+/2) mice may involve activation of the MCP-1/CCR2 pathway and infiltration of T cells and macrophages. 16 Although we cannot exclude the contribution of hypertension to renal impairment in KL(+/2) mice, consistent results of other studies without the confounding interference of hypertension 7,40,41 suggest that the activated inflammatory process could play an independent and important role in renal damage.…”
Section: Discussionsupporting
confidence: 64%
“…38,39 Our recent study showed that high salt-induced kidney damage in KL(+/2) mice may involve activation of the MCP-1/CCR2 pathway and infiltration of T cells and macrophages. 16 Although we cannot exclude the contribution of hypertension to renal impairment in KL(+/2) mice, consistent results of other studies without the confounding interference of hypertension 7,40,41 suggest that the activated inflammatory process could play an independent and important role in renal damage.…”
Section: Discussionsupporting
confidence: 64%
“…[24][25][26][27][28] Importantly, the aldosterone-induced damage to the heart and kidneys is largely independent of the systemic effects on blood pressure. 10,29 Inflammation and fibrosis seem to play central roles in the pathophysiology of both cardiac and renal aldosteroneinduced injury. In response to treatment with aldosterone and salt, rat myocardium displays increased inflammation and upregulated expression of proinflammatory cytokines, such as tumor necrosis factor-α, interleukin-1β, and transforming growth factor-β1 (TGF-β).…”
Section: February 2015mentioning
confidence: 99%
“…31 These effects may be mediated by serum-and glucocorticoid-induced protein kinase-1 and transcription factors nuclear factor-κB and activator protein-1, the expression and activity of which, respectively, are stimulated by aldosterone/salt or angiotensin II/salt in animal heart and kidneys. [29][30][31][32][33] Kidney biopsies from patients with high albuminuria show significant increases in the expression of serum-and glucocorticoid-induced protein kinase-1 and the inflammatory mediators macrophage chemoattractant protein-1, TGF-β, and The direct deleterious effects of aldosterone/MR activation in the heart and kidneys and the common pathophysiological mechanisms involved. The benefits of MRAs in interrupting these pathways are also illustrated.…”
Section: February 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Ald is associated with cellular oxidative stress, 7,8 inducing both glomerular and tubulointerstitial injury in the salt-sensitive hypertension model. [9][10][11][12] As tubulointerstitial damage is strongly associated with the prognosis of CKD, 13,14 a new strategy with antioxidant activity is needed for preventing the progression of such damage due to hypertension.…”
Section: Introductionmentioning
confidence: 99%